The Genetic parameters of fertility traits in Murrah buffaloes: Estimate Genetic parameters - Sharma, Smriti; Dhaka, Surender; Patil, Chandrashekhar Santosh (Indian Journal of Dairy Science, 2023)
The data pertaining to 662 Murrah buffaloes of 24 years (1996-2019) collected from history cum pedigree sheets maintained at Buffalo Farm, department of LPM, LUVAS, Hisar studied to determine the influence of non-genetic factors viz. period, season and parity and to estimate the genetic parameter of fertility performance traits using mixed linear model. The traits studied wereage at first calving (AFC), service period (SP), conception rate (CR), calving interval (CI), number of services per conception (NSC) and pregnancy rate (PR). Period of calving had non-significant effect on all fertility traits viz. SP, CR, CI, NSC and PR, except AFC. Season of calving reported to have highly significant (P